BIOKINEMATIC CHARACTERISTICS OF THE TRIPLE JUMP TECHNIQUE IN QUALIFIED ATHLETES - Vladyslav Rozhkov; Arkadiusz Stanula; Liliana Riadova; Daria Okun; Svitlana Stadnyk (Kharkiv State Academy of Physical Culture, 2024)
The purpose of the study is to investigate the biokinematic characteristics of the triple jump technique in qualified athletes. Material and methods. The technique of the final attempts of qualified triple jumpers during the 2023 World Athletics Championships was analyzed. The following methods were used in the work: analysis and synthesis of scientific and methodological literature, analysis of video materials, methods of mathematical statistics. The video of the final attempts was used, provided for public use by the International Athletics Federation (World Athletics). The attempts were recorded by four video cameras installed on the side of the treadmill at a distance of 2,5 m, the height of the video camera mounted on a tripod was 1,5 m. Two of the four video cameras recorded video at a frequency of 25 frames per second, the other two video cameras recorded video at a frequency of 1300 frames per second. Video analysis of the final attempts and processing of biokinematic parameters of the technique were determined using the Dartfish and Kinovea programs. All statistical data were processed in the statistical analysis program IBM SPSS Statistics version 28.0.1.0. Results. The metric, time, angular, and speed characteristics of the take-off technique are determined; push-off; jump; step; jump for highly skilled triple jumpers. Based on the analysis of the triple jump technique indicators, the optimal biokinematic parameters of the technique that athletes need to have in order to achieve high competitive results were obtained. Conclusions. To achieve high competitive results in the triple jump, the following technical parameters must be used. The take-off speed should reach 10.40 m s-1 or more, the length of the last take-off step should be 2,20-2,40 m; the pace of the last step is 4-5 steps/s. The push-off; from the bar should last 0.100-0.133 s; the push-off; angle reaches 65-70 ̊; the speed of departure of the general center of mass of the body is 9.60 m s-1 and more. The jump should last no more than 0,660 s. During the jump, the high height of the overall center of body mass should be 1.30-1.45 m; upon landing, the speed of the general center of mass of the body is 9,20 m s-1 or more. The second push-off should last 0,160-0,180 s, the push-off angle is 60-65°. The take-off speed of the general center of body mass in a step should be 8,80 m s-1 or more. The optimal step duration is 0.450-0.520 s, step length is 5.20-5.50 m, the maximum height of the overall center of body mass is 1.24-1.30 m; upon landing, the speed of the general center of mass of the body is 8.50 m s-1 or more. The third push-off should last 130-166 s. The push-off angle is 63-70°. The take-off speed of the general center of mass of the body in a jump is from 8 m s-1 and more. The optimal duration of the jump is 0.750-0.780 s; maximum height of the overall center of body mass 1,10-1,22 m; upon landing, the speed of the general center of mass of the body is 7 m s-1 or more. When taking off and landing, the angle in the supporting leg throughout all three jumps should be 163-170 ̊.